Identifying Metaphorical Word Use with Tree Kernels - Hovy, Dirk; Srivastava, Shashank; Jauhar, Sujay Kumar; Sachan, Mrinmaya; Goyal, Kartik; Li, Huiying; Sanders, Whitney; Hovy, Eduard (2013)
A metaphor is a figure of speech that refers to one concept in terms of another, as in “He is such a sweet person”. Metaphors are ubiquitous and they present NLP with a range of challenges for WSD, IE, etc. Identifying metaphors is thus an important step in language understanding. However, since almost any word can serve as a metaphor, they are impossible to list. To identify metaphorical use, we assume that it results in unusual semantic patterns between the metaphor and its dependencies. To identify these cases, we use SVMs with tree-kernels on a balanced corpus of 3872 instances, created by bootstrapping from available metaphor lists.1 We outperform two baselines, a sequential and a vectorbased approach, and achieve an F1-score of 0.75.